Excel 2016 formulas - Alexander, Michael 1972-; Kusleika, Dick (Wiley, 2016)
Annotation
Includes index. - Online resource; title from PDF title page (EBSCO, viewed January 14, 2016)
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets -- Computer programs; Tableurs; Logiciels; COMPUTERS; Desktop Applications; Spreadsheets; Electronic spreadsheets; Computer programs